2008
DOI: 10.1179/crn.2008.003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Tooth Grinding Pattern During Sleep Bruxism and Temporomandibular Joint Status

Abstract: The purpose of this study was to investigate the relationship between tooth grinding pattern during sleep bruxism and temporomandibular joint (TMJ) status based on condylar movement. Fifty subjects (21 males and 29 females) wore a bruxism recording device, BruxChecker, to record their grinding pattern during sleep bruxism. The grinding pattern was categorized into laterotrusive grinding (LG) and mediotrusive side grinding (MG). Furthermore, LG was divided into three types; incisor-canine (IC), incisor-canine-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 17 publications
2
14
1
4
Order By: Relevance
“…They called it the "Weak Link Theory". Current results [36,37] also suggested that bruxism with molar contacts was responsible not only for the diseases affecting the teeth and periodontal structures, but also for TMJ dysfunction, which partly supports the Weak Link Theory.…”
Section: Bruxism and Oral Diseasementioning
confidence: 54%
“…They called it the "Weak Link Theory". Current results [36,37] also suggested that bruxism with molar contacts was responsible not only for the diseases affecting the teeth and periodontal structures, but also for TMJ dysfunction, which partly supports the Weak Link Theory.…”
Section: Bruxism and Oral Diseasementioning
confidence: 54%
“…This prevents muscle hyperactivity by evenly distributing the forces of the masticatory and associated muscles. [19][20][21] The occlusal scheme, which includes the spatial position of the occlusal plane, plays a very important role in these tasks. 22 It is evident that a sequentially guided occlusion with canine dominance leads to posterior dis-occlusion, the avoidance of protrusive, laterotrusive, and mediotrusive posterior dental interferences and seems to be best suited for providing undisturbed function of the neuro-muscular system.…”
Section: Guest Editorialmentioning
confidence: 99%
“…En odontología, la evaluación funcional de la oclusión en estática y dinámica es de gran importancia, por cuanto de ella dependen, en gran parte, el éxito o el fracaso de cualquier tratamiento dentro del ámbito de cualquier especialidad. El examen clínico es el método que más se utiliza para valorar los patrones oclusales, pero tiene la limitante de ser realizado en vigilia, cuando el paciente controla la expresión real de los verdaderos contactos que se generan durante el sueño (1,2). Así, el patrón oclusal puede verse alterado y, en algunos casos, asociado al desgaste dental, consecuencia de trastornos del sueño, como el bruxismo, ampliamente definido como un tipo de movimiento estereotipado caracterizado por el rechinamiento y apretamiento de los dientes durante el sueño, que se considera una actividad parafuncional (3)(4)(5)(6).…”
Section: Introductionunclassified
“…Otros estudios han reportado el uso del Bruxchec-ker® como herramienta en la detección de patrones oclusales asociados al sueño utilizando diferentes criterios de evaluación y clasificación (1,2,(14)(15)(16)(17)(18)(19)(20)…”
Section: Introductionunclassified